Prophetic Rationality as Educational Philosophy: A Hadith-Based Reconsideration of Knowledge and Action - Aji Abdullah; Pujiono; Wasi’un; Andri Nirwana (Green Publisher, 2025)
This study aims to review prophetic rationality as the foundation of Islamic educational philosophy by examining the structure of knowledge and action derived from the hadiths of the Prophet Muhammad SAW. The phenomenon underlying this research is the tendency of contemporary Islamic education to be predominantly normative-textual and lacking in philosophical reflection, thus failing to bridge revelation, reason, and social praxis. The research approach used is qualitative library research with a philosophical hermeneutic analysis method. Data were collected from primary literature (hadith books and their commentary) and secondary literature (scientific articles, books, and works of classical and contemporary Islamic educational thinkers). The results of the analysis show three main findings: (1) A prophetic epistemology based on revelation that integrates reason (‘aql), heart (qalb), and revelation (wahy) as the basis for the formation of knowledge; (2) A transformative axiology of prophetic education, rooted in the values ??of justice (‘adl), liberation (ta?r?r), and humanization (ins?niyyah); and (3) Integration of knowledge and practice that makes education a process of internalizing values ??and social transformation through exemplary behavior (uswah ?asanah). These findings expand the discourse on Islamic educational philosophy by offering an epistemological and practical framework derived from the hadith, as well as providing theoretical and practical contributions to the design of Islamic curriculum and pedagogy. This study recommends further exploration of the application of prophetic values ??in the context of multicultural and inclusive education, in order to strengthen the relevance of the hadith as an adaptive and transformative educational resource in the modern era.